Residues of grape ( Vitis vinifera L.) seed oil production as a valuable source of phenolic antioxidants - Maier, Thorsten; Schieber, Andreas; Kammerer, Dietmar R.; Carle, Reinhold (Food chemistry, 2009)
Phenolic compounds of seven grape seed samples originating from mechanical seed oil extraction were identified and quantified by HPLC–DAD before (intact seeds) and after (press residue) the oil recovery process. Total amounts of all identified compounds ranged from 4.81 (‘Cabernet Mitos’) to 19.12 g/kg (‘Schwarzriesling’) of defatted dry matter (DM; ‘Schwarzriesling’) for integral grape seeds, whereas their content in the press residues ranged from 2.80 (‘Cabernet Mitos’) to 13.76 g/kg of defatted DM (‘Spätburgunder’). This is the first study presenting comprehensive data on the contents of individual phenolic compounds comprising all polyphenolic subclasses of press residues from grape seed oil production also covering the determination of the antioxidant activities of each subclass (Folin–Ciocalteu, FRAP and TEAC assays). Additionally, the effects of different solvents on the yields of phenolic compounds were determined. Maximum yields were obtained using methanol/0.1% HCl ( v:v), water [75 °C] and a mixture of ethanol and water [3:1; v:v], respectively, whereas pure ethanol resulted in poor polyphenol extraction. The results of the present study confirm the press residues of grape seed oil production still to be a rich source of polyphenolics with strong antioxidant activity.